Tradisi Qada Shalat Berjamaah Setelah Shalat Tarawih Di Masjid Baiturrohmah Jekulo Pulutan Kudus (Living Qur’an): The Tradition of Qada Congregational Prayer After Tarawih Prayer at the Baiturrohmah Jekulo Pulutan Kudus Mosque (Living Qur'an) - Arina Fazatin Nafala; Abdul Karim (Ulumul Qur'an: Jurnal Kajian Ilmu Al-Qur'an dan Tafsir, 2025)
This study aims to examine: first, the history of the tradition of congregational qada prayers. Second, the implementation of the tradition of congregational qada prayers. Third, the wisdom behind the tradition of congregational qada prayer. The main issue in this study is the practice of congregational qada prayer, which has not been studied in depth, both in terms of history, implementation, and the values contained therein, as well as the controversy surrounding the permissibility of congregational qada prayer in the perspective of Islamic law. The method used in this study is descriptive qualitative research using a descriptive approach and ethnographic study. This research was conducted at the Baiturrohmah Mosque in Jekulo Pulutan Village. Data collection was carried out using interviews, observation, and documentation, and then described using data reduction, data presentation, verification, and conclusions. After that, several techniques were used to test the validity of the data, including extension, participation, persistence of observation, and triangulation. The results of this study show that, first, this tradition originated from the example set by Kyai Noor Hadi's teacher, Mbah Yasin, to emphasize the importance of fulfilling religious obligations, including missed fardhu prayers. Second, congregational qada prayers do not contain elements of bid’ah and include tarekat practices, including the Syattariyah and Rifaiyyah tarekat. Third, the social and spiritual dimensions found in the tradition of congregational qada prayers include an increase in spiritual values and improvement in worship, humanism, friendship and socialization, the distribution of alms and humility, and physiological and psychological improvement.